Implementing Universal and Targeted Policies for Health Equity: Lessons From Australia - Matthew Fisher; Patrick Harris; Toby Freeman; Tamara Mackean; Emma George; Sharon Friel; Fran Baum (Kerman University of Medical Sciences, 2022)
Background  Debate continues in public health on the roles of universal or targeted policies in providing equity of access to health- related goods or services, and thereby contributing to health equity. Research examining policy implementation can provide fresh insights on these issues.Methods  We synthesised findings across case studies of policy implementation in four policy areas of primary healthcare (PHC), telecommunications, Indigenous health and land use policy, which incorporated a variety of universal and targeted policy structures. We analysed findings according to three criteria of equity in access - availability, affordability and acceptability - and definitions of universal, proportionate-universal, targeted and residual policies, and devolved governance structures.Results  Our analysis showed that existing universal, proportionate-universal and targeted policies in an Australian context displayed strengths and weaknesses in addressing availability, affordability and acceptability dimensions of equity in access.Conclusion  While residualist policies are unfavourable to equity of access, other forms of targeting as well as universal and proportionate-universal structure have the potential to be combined in context-specific ways favourable to equity of access to health-related goods and services. To optimise benefits, policies should address equity of access in the three dimensions of availability, affordability and acceptability. Devolved governance structures have the potential to augment equity benefits of either universal or targeted policies.